Project “BUSSARD” − a holistic development of high-efficiency solar cells covering innovative front-end, metallization and interconnection approaches - Lorenz Andreas; Schube Jörg; Nikitina Veronika; Mack Sebastian; Schweigert Sebastian; Buddgard Jonas; Albrecht Jonas; Pospischil Maximilian; Kraft Achim; Wolf Andreas; Hermle Martin; Clement Florian (EPJ Photovoltaics, 2025)
Within this work, we present key results of the transnational European research project “Bussard”. The aim of this project is the development and evaluation of various innovative approaches for highly efficient cell concepts such as tunnel oxide passivating contact (TOPCon) solar cells considering the whole process chain including front-end, back-end and module processing. We present atomic layer deposition (ALD) as a high-throughput alternative for the deposition of Al2O3 passivation layers on the front side of TOPCon solar cells enabling a substantial reduction of the emitter saturation current density down to j0e = 13 fA/cm2. In the field of metallization, we evaluate and demonstrate three innovative approaches for the fine-line metallization of TOPCon solar cells. In this study we focus on multi-nozzle parallel dispensing, a technology that was developed as an alternative to standard screen-printing metallization and is used for the metallization of TOPCon solar cells for the first time. By optimizing the fabrication process at Fraunhofer ISE, we realize TOPCon solar cells (156.75 mm × 156.75 mm) with a champion conversion efficiency of up to ηmax = 24.2% (independently confirmed by Fraunhofer ISE CalLab PVCells). Finally, we present a comprehensive evaluation of the innovative Tape Solution interconnection concept for TOPCon cells and modules. We demonstrate the feasibility on small-scale and full-format modules and analyze the I–V results as well as cell-to-module (CTM) loss analysis using the simulation tool SmartCalc®. The results are compared to TOPCon modules interconnected via SmartWire Connection Technology (SWCT) and electrically conductive adhesive (ECA).